1035. Patient-Reported Outcomes on Long-Acting Cabotegravir + Rilpivirine as Maintenance Therapy: FLAIR 96-Week Results. (31st December 2020) - Chounta, Vasiliki; Bernal, Enrique; Lombaard, Johan; Katner, Harold P; Walmsley, Sharon; Dorey, David; Spreen, William; Griffith, Sandy; Margolis, David
Abstract: Background: In the phase 3 FLAIR study, switching to monthly injectable long-acting (LA) cabotegravir (CAB) + rilpivirine (RPV) was noninferior to continued daily oral dolutegravir/abacavir/lamivudine (DTG/ABC/3TC) for the maintenance of virologic suppression over 96 weeks in adults with HIV-1. Key patient-reported outcomes (PROs) through Week 96 are presented. Methods: In FLAIR, ART-naive adult participants received induction therapy with oral DTG/ABC/3TC for 20 weeks. Those with HIV-1 RNA < 50 c/mL at 16 weeks were randomized (1:1) to continue DTG/ABC/3TC or receive monthly CAB + RPV LA injections after a 4-week lead-in with daily oral CAB + RPV through Week 96. Treatment satisfaction (HIV Treatment Satisfaction Questionnaire status version [HIVTSQs]) and acceptability of injections (Perception of Injection [PIN] Questionnaire) up to Week 96 were secondary endpoints. Results: A total of 566 participants were randomized (median age, 34 years; 22% female); baseline characteristics were similar between treatment groups. At Week 96, significantly greater improvement from baseline in total treatment satisfaction score was observed in the CAB + RPV LA vs DTG/ABC/3TC treatment group (adjusted mean difference, 2.3 [95% CI, 1.1-3.5]; P < 0.001), further increasing from Weeks 24 (2.1 [0.9-3.3]) and 44 (0.7 [−0.4, 1.9]). Key drivers for the difference in HIVTSQs between treatment groups were items assessing convenience, flexibility, and satisfaction to continue with LA therapy. In participants receiving CAB + RPV LA, mean score for the "Acceptability of ISRs" dimension of PIN (scale, 1-5) significantly decreased (improved) from Week 5 to Weeks 41, 48, and 96 (2.08 to 1.71, 1.66, and 1.71, respectively; P < 0.001 for all). In addition, 82% and 85% of LA participants, respectively, rated pain and local reactions due to injections as "totally" or "very acceptable" at Week 96. Conclusion: At Week 96, FLAIR participants receiving LA therapy reported greater improvement in treatment satisfaction compared with participants continuing on daily oral medication as well as overall good acceptability of injections with improvement over time. Overall, these results support monthly CAB + RPV LA as an alternative to daily oral regimens for adults with HIV-1. Disclosures: Vasiliki Chounta, MSc, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) Sharon Walmsley, FRCPC, MD, MSC, GSK (Grant/Research Support)ViiV Healthcare (Grant/Research Support) David Dorey, MMATH, GlaxoSmithKline Inc. (Employee, Shareholder) William Spreen, PharmD, ViiV Healthcare (Employee, Shareholder) Sandy Griffith, PharmD, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee) David Margolis, MD, MPH, GlaxoSmithKline (Shareholder)ViiV Healthcare (Employee)